SISTEM PAKAR MODEL FUZZY EVALUASI KINERJA PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA BONTANG - Maagus Mochammad Yusuf (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
The distribution and filling of questionnaires which have not computerized cause the excessive of paper usage. Some of the impacts of those cases were: the occurrence of error in the process of conducting a survey, the high costs of survey, the lack of accurate data in survey calculation result, less secure of data survey storage, the difficulty in accessing the data and information about community satisfaction rate, and a lot of time required in the process of arranging the data. The system aimed to produce a design and built an Information System of Services Assessment in Population and Civil Registration Agency in Bontang City using Fuzzy Sugeno. This system will improve Service Unit Performance in Population and Civil Registration Agency in Bontang City. The result of this research by input, fuzzyfication, reasoning, defuzzyfication, output, showed that the resulting scores had truth analysis based on the Community Satisfaction Survey in the first and second semester of 2015, with score 77.78, the service quality was B, and the service unit performance was good. Keywords: Information System, Fuzzy Sugeno, Evaluation Service.